2014
DOI: 10.1007/s12298-014-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Zinc stress induces physiological, ultra-structural and biochemical changes in mandarin orange (Citrus reticulata Blanco) seedlings

Abstract: Zinc (Zn) is an essential micronutrient for higher plants; yet, at higher concentrations it is toxic. In order to explore the effect of Zn stress on growth, biochemical, physiological and ultra-structural changes, 1 year old mandarin plants were grown under various Zn concentrations (1, 2, 3, 4, 5, 10 15 and 20 mM) for 14 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 59 publications
5
37
0
1
Order By: Relevance
“…However, a significant reduction in SOD and GR activities due to TIBA under Zn deficiency indicated crosslink between auxin signaling and elevated antioxidant activities in roots of Pokkali. To withstand abiotic stresses, plants adapt antioxidant defense for restoring redox metabolism and cellular turgor (Subba et al 2014;Kabir et al 2015). Our results also indicated that auxin might be helpful for keeping SOD balance in plants.…”
Section: Discussionmentioning
confidence: 53%
“…However, a significant reduction in SOD and GR activities due to TIBA under Zn deficiency indicated crosslink between auxin signaling and elevated antioxidant activities in roots of Pokkali. To withstand abiotic stresses, plants adapt antioxidant defense for restoring redox metabolism and cellular turgor (Subba et al 2014;Kabir et al 2015). Our results also indicated that auxin might be helpful for keeping SOD balance in plants.…”
Section: Discussionmentioning
confidence: 53%
“…The concentrations of heavy metals in the MSWVC amended soils were found in the order of Fe > Zn > Cu > Cr > Ni > Pb > Cd. Zn is an important micronutrient for different metabolic functions in plants; however, it's toxic levels in soil lead to reduced plant growth, leaf chlorosis, photosynthesis impairment, and reactive oxygen species (ROS) production that poses harm to membrane integrity and permeability (Cambrollé et al 2012, Subba et al 2014, Srivastava et al 2017. Moreover, high concentrations of Zn adversely affect dehydrogenase, β-D-glucosidase, urease, catalase, and invertase activities in soil (Kunito et al 2001, Yang et al 2006, Ciarkowska et al 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Other non-enzymatic metabolites like MDA, proline and ascorbic acid also reversed their accumulation behavior in Zn supplemented Zn-Cd combination treatment compared to Cd only treatments. Addition of Zn to Cd stressed plants helps in lowering MDA content and proline accumulations (Khalid and Hendawy, 2005;Subba et al, 2014;Qiao et al 2015). Zn supplementation lowers the abiotic stress including that of heavy metal Cd by raising ascorbic acid levels (Ozturk et al, 2003Seminario et al, 2017).…”
Section: Discussionmentioning
confidence: 99%